PENGARUH PACKAGE ICING TERINTERUPSI TERHADAP MUTU BROKOLI (Brassica oleracea, L.) SELAMA PENYIMPANAN - I Putu Agus Oka Mahendra; I. A. Rina Pratiwi Pudja; Gede Arda (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2016)
The aims of this study were to determine the effect of interrupted package icing broccolis on product’s quality and to obtain the best treatment that can be applied to maintain the shelf life of product. Fresh broccolis were stored in Styrofoam box covered by ice for period of time and then move to refrigerated showcase. The research consists of five treatments based on ratio time in Styrofoam box and display product. Comparison stored broccolis in Styrofoam box with ice and display product on show case; 12:12 (P2), 15:9 (P3), 18:6 (P4), 21:3 (P5). Other treatment is stored broccolis in Styrofoam box without ice and display product on room temperature with comparison time; 12:12 (P1). Every treatment was repeated every day until the broccoli reached the unacceptable quality according to panelist’s perception. Measured parameters including percentage of weight loss, respiration rate, color difference and the shelf life of broccoli. The results showed that longer time storage broccoli in Styrofoam box with ice smaller the weight difference. P5 have lowest consumption rate of oxygen of 62.63 ml/.kg.hr and lowest carbon dioxide production rate of 62.57 ml/.kg.hr. The color difference ∆Eab less than 9.73 indicated that broccoli’s floret was still green based on the panelists scoring, therefore it was still acceptable. Higher color difference’s poin and panelists scoring, broccoli was broken and not accepted in the market. In conclusion, the treatments only maintained the broccoli for five days of storage.